2022
DOI: 10.1001/jamaoto.2022.1638
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inferior Turbinate Hypertrophy and Extraesophageal Reflux

Abstract: To the authors' knowledge, no prior studies have examined the association between inferior turbinate hypertrophy (ITH) and extraesophageal reflux (EER). If EER were a cause or cofactor of ITH, antireflux treatment can be considered prior to surgical intervention. OBJECTIVE To evaluate EER presence and severity in patients with different degrees of ITH. DESIGN, SETTING, AND PARTICIPANTSProspective multicentric cohort study conducted at 3 referral centers treating patients with EER and certified for 24-hour moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In 2020, Lechien et al supplemented the endoscopic picture of the larynx under the influence of laryngopharyngeal reflux by describing changes on the pharyngeal side [5]. In 2022, Zeleník et al identified a relationship between hypertrophy of the Inferior Turbinate and extraesophageal reflux [6]. The aim of our study is to determine the characteristics of the endoscopic picture of the nose and nasopharynx in chronic rhinosinusitis associated with symptoms of gastroesophageal acid reflux disease.…”
Section: Introductionmentioning
confidence: 96%
“…In 2020, Lechien et al supplemented the endoscopic picture of the larynx under the influence of laryngopharyngeal reflux by describing changes on the pharyngeal side [5]. In 2022, Zeleník et al identified a relationship between hypertrophy of the Inferior Turbinate and extraesophageal reflux [6]. The aim of our study is to determine the characteristics of the endoscopic picture of the nose and nasopharynx in chronic rhinosinusitis associated with symptoms of gastroesophageal acid reflux disease.…”
Section: Introductionmentioning
confidence: 96%
“…24 Only a few studies have addressed the relationship between EER and mucosal hypertrophy of the inferior nasal turbinate. 25,26 However, no prior research has objectively examined the possible effect of acidic pH environment on mulberry posterior inferior nasal turbinate formation. Therefore, this prospective study is aimed to investigate whether mulberry formation of the posterior inferior nasal turbinate is associated with acidic pH events monitored by 24-h oropharyngeal pH monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have addressed the relationship between EER and mucosal hypertrophy of the inferior nasal turbinate 25,26 . However, no prior research has objectively examined the possible effect of acidic pH environment on mulberry posterior inferior nasal turbinate formation.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor Zeleník and colleagues have reported a possible association between inferior turbinate hypertrophy and extraesophageal reflux (EER). They also highlight previously reported associations of EER with chronic rhinosinusitis and chronic otitis media.…”
mentioning
confidence: 99%
“…The authors comment on the challenges of measuring pepsin and/or pH in the nasal cavity. Improvements in technique will benefit each line of inquiry and investigators should consider following the parallel progress.…”
mentioning
confidence: 99%